2015
DOI: 10.1016/j.ramd.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index and cardiorespiratory fitness as predictor of health status in schoolchildren

Abstract: a b s t r a c tObjective: Evaluate the cardiorespiratory fitness (CRF) and the body mass index (BMI) of schoolchildren according to the cutoff points established by the Fitnessgram ® . Just as determine the influence of BMI on CRF in children and propose an equation for predicting VO 2 max from the body composition. Method: The sample consisted of 288 students of basic level of public education in the city of AracajuSergipe -Brazil, aged between 10 and 14 years, of these, 142 were female. To evaluate the CRF t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…9 The difference in measurement method could explain the different result with our study, because although indirect method is valid and more feasible, direct method still has the best accuracy in assessing VO2max. 20 Similar finding was shown in the study by Bonney et al 10 (r = -0.336, p < 0.001) among 151 adolescent girls and Hingorjo et al 11 (r = -0.558, p < 0.001 in males, r = -0.246, p < 0.028 in females) among 133 young adults, and De Araujo et al 12 (r 2 = 0.907, p = 0.026 in girls, r 2 = 0.850, p = 0.012 in boys) among 288 children. On the contrary, a study conducted by Hawari et al found a significant but weak positive relationship (β = 0.11, p = 0.000) between BMI and duration of cardiopulmonary exercise testing in 138 study subjects consisted of waterpipe tobacco smokers and non-smokers.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…9 The difference in measurement method could explain the different result with our study, because although indirect method is valid and more feasible, direct method still has the best accuracy in assessing VO2max. 20 Similar finding was shown in the study by Bonney et al 10 (r = -0.336, p < 0.001) among 151 adolescent girls and Hingorjo et al 11 (r = -0.558, p < 0.001 in males, r = -0.246, p < 0.028 in females) among 133 young adults, and De Araujo et al 12 (r 2 = 0.907, p = 0.026 in girls, r 2 = 0.850, p = 0.012 in boys) among 288 children. On the contrary, a study conducted by Hawari et al found a significant but weak positive relationship (β = 0.11, p = 0.000) between BMI and duration of cardiopulmonary exercise testing in 138 study subjects consisted of waterpipe tobacco smokers and non-smokers.…”
Section: Discussionsupporting
confidence: 70%
“…Most studies found a negative association between both variables but some studies had different results. [9][10][11][12][13][14][15][16][17][18] The objective of this study is to analyze the association between BMI and CRF that is measured by cardiac stress test.…”
Section: Introductionmentioning
confidence: 99%
“…This result also was observed in previous research on children and adolescents in which the greater the BMI, the lower the VO2max. 40,41 In model 2, VO2max could be estimated by only 6MWD (R 2 = 0.51, SEE = 4.17 mL/kg/miñ 10% of the mean VO2max, P < .001). This result was consistent with previous research in which the greater the 6MWD, the greater the VO2max in children and adolescents.…”
Section: Original Articlesmentioning
confidence: 99%
“…Differences between the subjects in these studies (healthy vs. sick) may explain the inconsistent results. According to the studies, the most important variables affecting VO2peak are weight and BMI (27,28).…”
Section: Discussionmentioning
confidence: 99%